Carbon-coated graphite negative electrode material, preparation method thereof, negative electrode sheet, battery, and electric device

CN122992072APending Publication Date: 2026-10-27HUIZHOU EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611363182.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

目前,商业化锂离子电池负极材料以人造石墨为主,其通常由焦炭前驱体经造粒形成尺寸为10~25微米的二次颗粒,此设计虽然有利于提高体积能量密度,但是大尺寸二次颗粒导致锂离子在石墨晶格内固相扩散路径过长,导致充电过程中产生浓差极化,不仅限制了充电速度,还可能带来析锂的安全隐患

Benefits of technology

[0004]本申请旨在至少在一定程度上解决相关技术中的技术问题之一。为此,本申请提出一种碳包覆石墨负极材料及其制备方法、负极片、电池、用电装置,该碳包覆石墨负极材料具有优异的快充性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992072A_ABST
    Figure CN122992072A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of batteries, and discloses a carbon-coated graphite negative electrode material, which comprises carbon-coated graphite negative electrode material particles, the carbon-coated graphite negative electrode material particles comprise a graphite inner core and a carbon coating layer, wherein the carbon coating layer has a hierarchical pore structure, the hierarchical pore structure comprises micropores and mesopores, and the carbon coating layer is doped with nitrogen elements. The carbon-coated graphite negative electrode material has excellent fast-charging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, specifically relating to carbon-coated graphite anode materials and their preparation methods, anode sheets, batteries, and electrical devices. Background Technology

[0002] With the rapid development of new energy vehicles and consumer electronics, the market has placed higher demands on the fast charging capabilities of lithium-ion batteries. Graphite, with its excellent conductivity, chemical stability, and cost advantages, has become the most widely used anode material in commercial lithium-ion batteries. Currently, commercial lithium-ion battery anode materials are mainly composed of artificial graphite, which is typically formed from coke precursors through granulation into secondary particles with a size of 10-25 micrometers. While this design is beneficial for improving volumetric energy density, the large size of the secondary particles results in an excessively long solid-phase diffusion path for lithium ions within the graphite lattice, leading to concentration polarization during charging. This not only limits the charging speed but may also pose a safety hazard of lithium plating.

[0003] To improve fast-charging performance, carbon-coated graphite materials have been developed in related technologies. Amorphous carbon coatings, with their large interlayer spacing and abundant structural defects, can provide more lithium-ion transport channels and storage sites, thereby enhancing fast-charging capabilities. However, carbon coatings formed by traditional coating methods are typically continuous and dense, which can hinder lithium-ion transport channels, making it difficult to achieve an ideal balance between the ion transport rate (i.e., rate performance) required for fast charging and interface stability. Therefore, developing a negative electrode material with excellent fast-charging performance without affecting other properties remains one of the current challenges. Summary of the Invention

[0004] This application aims to at least partially solve one of the technical problems in the related art. To this end, this application proposes a carbon-coated graphite anode material and its preparation method, anode sheet, battery, and power device, wherein the carbon-coated graphite anode material has excellent fast-charging performance.

[0005] In a first aspect, this application proposes a carbon-coated graphite anode material, comprising carbon-coated graphite anode material particles, wherein the carbon-coated graphite anode material particles include a graphite core and a carbon coating layer, wherein the carbon coating layer has a multi-level porous structure, the multi-level porous structure including micropores and mesopores, and the carbon coating layer is doped with nitrogen.

[0006] In this application, the carbon coating layer of the carbon-coated graphite anode material possesses a microporous structure, which is crucial for enhancing the battery's fast-charging performance. Specifically, the mesopores in the carbon coating layer can be fully wetted by the electrolyte, creating high-speed ion channels that allow lithium ions to rapidly and unimpededly cross the carbon coating layer to reach the graphite core surface for insertion / extraction. This significantly reduces transport resistance and shortens lithium ion migration time. Meanwhile, the micropores in the carbon coating layer provide ample lithium ion adsorption sites, buffering ion concentration gradients during fast charging, alleviating concentration polarization, and providing more interfacial reaction sites to improve reaction kinetics and ensure a stable supply of lithium ions during fast charging. The synergistic effect of these two aspects greatly improves the shortcomings of anode materials in related technologies (such as long ion diffusion paths and low ion transport rates). Meanwhile, the carbon coating layer with microporous structure is doped with nitrogen, which further introduces a large number of defects into the lattice of the carbon coating layer. These defects can serve as adsorption sites for lithium ions, thereby helping to further enhance its fast charging performance. On the other hand, nitrogen doping sites can also adsorb impurity ions in the electrolyte, inhibiting the excessive growth of the SEI film. While improving fast charging performance, it also takes into account interface stability and cycle life.

[0007] In addition, the carbon-coated graphite anode material according to the above embodiments of this application may also have the following additional technical features: In some embodiments, the carbon-coated graphite anode material satisfies at least one of the following conditions: The thickness of the carbon coating layer is 100nm~200nm; The pore size of the micropores in the carbon coating layer is <2nm; The pore size of the intermediate pores in the carbon coating layer is 2nm~30nm.

[0008] In some embodiments, at least one of the following conditions is met: The carbon-coated graphite anode material D 50 Particle size ranges from 10 μm to 30 μm; The specific surface area of ​​the carbon-coated graphite anode material is 2.0 m². 2 / g~3.5m 2 / g; The compaction density of the carbon-coated graphite anode material is 1.5 g / cm³. 3 ~1.9 g / cm 3 ; The degree of graphitization of the carbon-coated graphite anode material is 91%~95%.

[0009] In some embodiments, at least one of the following conditions is met: The carbon-coated graphite anode material retains ≥80% of its capacity after 300 cycles under a 3.0 C discharge rate. The full-cell system using the carbon-coated graphite anode material takes 12 to 14 minutes to charge from 0% to 80% at a 3.0 C rate.

[0010] A second aspect of this application provides a method for preparing the aforementioned carbon-coated graphite anode material, comprising: The first carbon source was graphitized under an inert atmosphere to obtain graphite particles. The graphite particles, the second carbon source, the nitrogen-containing precursor, the pore-forming agent, and the catalyst are subjected to a sol-gel reaction to obtain a first carbon-coated graphite precursor. The first carbon-coated graphite precursor was subjected to gradient curing under vacuum to obtain the second carbon-coated graphite precursor. The second carbon-coated graphite precursor is subjected to high-temperature carbonization to obtain a carbon-coated graphite anode material. This yields a carbon-coated graphite anode material with excellent fast-charging performance.

[0011] In some embodiments, at least one of the following conditions is met: The mass ratio of the graphite particles, the second carbon source, the nitrogen-containing precursor, the porogen, and the catalyst is 100:(4~16):(0.3~3):(0.5~5):(0.1~1), preferably 100:(8~12):(0.5~2):(1~3):(0.2~0.8). The temperature for the graphitization treatment is 2800℃~3200℃; The graphitization process takes 5 to 20 hours. The temperature for the sol-gel reaction is 40℃~80℃; The sol-gel reaction time is 2h~12h; The high-temperature carbonization treatment is performed at a temperature of 800℃~1150℃. The high-temperature carbonization treatment lasts for 3 to 5 hours. The heating rate of the high-temperature carbonization treatment is 1.0℃ / min to 6.0℃ / min; The first carbon source includes at least one of oil-based needle coke and coal-based needle coke; The second carbon source includes at least one of phenolic resin, epoxy resin, polyimide resin, furan resin, asphalt, polyvinyl alcohol, and glucose; The nitrogen-containing precursor includes at least one of dicyandiamide, melamine, urea, and C3N4; The pore-forming agent includes at least one of polyethylene glycol 2000, polyvinyl alcohol, Pluronic F127, ammonium bicarbonate, and citric acid. The catalyst includes at least one of p-toluenesulfonic acid, oxalic acid, citric acid, hydrochloric acid, sulfuric acid, and phosphoric acid, preferably p-toluenesulfonic acid.

[0012] In some embodiments, subjecting the first carbon-coated graphite precursor to a gradient curing process under vacuum includes: The first carbon-coated graphite precursor is heated to a first temperature at a first heating rate and held for a first time under vacuum conditions. Heat to the second temperature at the second heating rate and hold for the second time; Heat to the third temperature at the third heating rate and hold for the third time.

[0013] In some embodiments, at least one of the following conditions is met: The first heating rate is 0.5℃ / min to 2℃ / min; The first temperature is 160℃~240℃; The first time period is 0.5h to 2h; The second heating rate is 0.5℃ / min to 2℃ / min; The second temperature is 360℃~520℃; The second time period is 1 hour to 3 hours; The third heating rate is 0.5℃ / min to 2℃ / min; The third temperature is 580℃~650℃; The third time period is 5h~8h; The vacuum conditions are -0.08 MPa to -0.06 MPa.

[0014] A third aspect of this application proposes a negative electrode sheet comprising the aforementioned carbon-coated graphite negative electrode material. Therefore, this negative electrode sheet exhibits excellent fast-charging performance.

[0015] A fourth aspect of this application provides a battery comprising the aforementioned carbon-coated graphite anode material or the aforementioned anode sheet. Therefore, this battery exhibits excellent fast-charging performance.

[0016] A fifth aspect of this application provides an electrical device comprising the aforementioned battery. This battery thus possesses excellent fast-charging performance and a long service life. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the structure of carbon-coated graphite anode material particles according to an embodiment of this application.

[0018] Figure 2 This is the N 1s spectrum of the carbon-coated graphite anode material of Example 1 of this application.

[0019] Figure 3 This is a pore size distribution diagram of the carbon coating layer in the carbon-coated graphite anode material of Embodiment 1 of this application.

[0020] Figure 4 This is a pore size distribution diagram of the carbon coating layer in the carbon-coated graphite anode material of Comparative Example 1 of this application. Detailed Implementation

[0021] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and intended to explain this application, and should not be construed as limiting this application.

[0022] The first aspect of this application discloses a carbon-coated graphite anode material, comprising carbon-coated graphite anode material particles, as shown in the reference. Figure 1 The carbon-coated graphite anode material particles include a graphite core 1 and a carbon coating layer 2, wherein the carbon coating layer has a multi-level pore structure, including micropores 2-1 and mesopores 2-2, and the carbon coating layer is doped with nitrogen.

[0023] In this application, the carbon coating layer of the carbon-coated graphite anode material possesses a microporous structure, which is crucial for enhancing the battery's fast-charging performance. Specifically, the mesopores in the carbon coating layer can be fully wetted by the electrolyte, creating high-speed ion channels that allow lithium ions to rapidly and unimpededly cross the carbon coating layer to reach the graphite core surface for insertion / extraction. This significantly reduces transport resistance and shortens lithium ion migration time. Meanwhile, the micropores in the carbon coating layer provide ample lithium ion adsorption sites, buffering ion concentration gradients during fast charging, alleviating concentration polarization, and providing more interfacial reaction sites to improve reaction kinetics and ensure a stable supply of lithium ions during fast charging. The synergistic effect of these two aspects greatly improves the shortcomings of anode materials in related technologies (such as long ion diffusion paths and low ion transport rates). Meanwhile, the carbon coating layer with microporous structure is doped with nitrogen, which further introduces a large number of defects into the lattice of the carbon coating layer. These defects can serve as adsorption sites for lithium ions, thereby helping to further enhance its fast charging performance. On the other hand, nitrogen doping sites can also adsorb impurity ions in the electrolyte, inhibiting the excessive growth of the SEI film. While improving fast charging performance, it also takes into account interface stability and cycle life.

[0024] In some embodiments, the pore size of the micropores in the carbon coating layer is <2 nm, specifically, it can be within the range of 0.01 nm, 0.05 nm, 0.1 nm, 0.2 nm, 0.4 nm, 0.6 nm, 0.8 nm, 1.0 nm, 1.2 nm, 1.4 nm, 1.6 nm, 1.8 nm, 1.9 nm, or any two of these ranges. The aforementioned pore size range can form stable adsorption sites, rapidly adsorbing and buffering lithium ions under high current during fast charging, alleviating local concentration gradients, and reducing concentration polarization and the risk of lithium plating.

[0025] In some embodiments, the pore size of the intermediate pores in the carbon coating layer is 2 nm to 30 nm, specifically, it can be 2 nm, 4 nm, 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, or any range between two of these. This pore size range is larger than the diameter of solvated lithium ions (approximately 0.6 to 0.8 nm), and can essentially ensure that the electrolyte fills quickly through capillary action, forming a continuous liquid phase transport channel, allowing lithium ions to pass through the coating layer without obstruction. If the pore size is too large (>30 nm), the channels may become discontinuous, and the density of the coating layer may decrease, failing to effectively isolate the electrolyte from the graphite core, resulting in poor interface stability.

[0026] In some embodiments, the thickness of the carbon coating layer is 100 nm to 200 nm, specifically, it can be 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, or any range between two of these. A carbon coating layer thickness within this range generally ensures the formation of a continuous coating layer on the graphite core surface, improving interface stability; simultaneously, it generally ensures that lithium ions have a high migration rate and relatively low transport resistance. This helps to balance the interface stability and fast-charging performance of the anode material.

[0027] In some embodiments, the graphitization degree of the carbon-coated graphite anode material is 91% to 95%. Specifically, the graphitization degree of the carbon-coated graphite anode material can be 91%, 92%, 93%, 94%, 95%, or any range between two of these. When the graphitization degree is too high (>95%), the graphite layers will be stacked too tightly, the interlayer spacing will be smaller, and the resistance to lithium-ion insertion / extraction will increase, which will affect the fast-charging performance to some extent. When the graphitization degree is too low (<91%), it may affect the capacity of the anode material. Therefore, limiting the graphitization degree to the above range can basically balance the capacity performance and fast-charging performance of the anode material.

[0028] Specifically, the method for testing the graphitization degree is as follows: First, the interlayer spacing (denoted as d) of the (002) crystal plane of the carbon-coated graphite anode material is accurately measured using an X-ray diffractometer. 002Then, substitute the values ​​into the Franklin formula (Mering-Maire formula) to calculate the degree of graphitization g: g = (0.3440) d 002 ) / (0.3440 0.3354)×100%, where 0.3440 nm is the interlayer spacing of a completely ungraphitized (random layer structure) structure, and 0.3354 nm is the interlayer spacing of an ideal graphite crystal.

[0029] In some embodiments, the carbon-coated graphite anode material D 50 The particle size is 10μm~30μm, specifically, it can be 10μm, 15μm, 20μm, 25μm, 30μm, etc. This is the D-type of carbon-coated graphite anode material. 50 Particle size within the above range is beneficial for ensuring a suitable contact area between the negative electrode material and the electrolyte, which can guarantee that there are enough adsorption sites to participate in the reaction, and will not cause too many side reactions due to excessive specific surface area.

[0030] Specifically, the aforementioned D 50 This means that 50% of the volume of particles is smaller than this particle size. This can be tested using a Malvern particle size analyzer. During testing, the instrument's opacity should be set to 10%. A suitable dispersant should be selected based on the particle size being tested, and samples should be taken gradually for analysis.

[0031] In some embodiments, the specific surface area of ​​the carbon-coated graphite anode material is 2.0 m². 2 / g~3.5m 2 / g, specifically, it can be 2.0m 2 / g, 2.2m 2 / g, 2.4m 2 / g, 2.6m 2 / g, 2.8m 2 / g, 3.0m 2 / g, 3.2m 2 / g, 3.5m 2 / g etc. A specific surface area within the above range helps to ensure the contact area between the negative electrode material and the electrolyte, promotes the electrochemical reaction, and improves the various electrochemical performances of the battery.

[0032] The specific surface area (BET) mentioned above refers to the total surface area per unit mass of carbon-coated graphite anode material. Specifically, it can be characterized using an ASAP2020 nitrogen surface adsorption-desorption analyzer. The specific testing methods are described in the examples below.

[0033] In some embodiments, the compaction density of the carbon-coated graphite anode material is 1.5 g / cm³. 3 ~1.9 g / cm 3Specifically, it can be 1.5 g / cm³. 3 1.6 g / cm 3 1.7 g / cm 3 1.8 g / cm 3 1.9 g / cm 3 When the compaction density is within the above range, it indicates that there is sufficient contact between the particles of the negative electrode material, which can ensure the electronic conductivity of the electrode, reduce the internal resistance of the electrode, promote the electrochemical reaction, and improve the electrochemical performance of the battery.

[0034] Specifically, compaction density is a physical parameter that measures the mass of a unit volume of a loose solid material (such as the carbon-coated graphite anode material particles mentioned above) after it has been compacted under external pressure. Essentially, it reflects the degree to which the voids between the material particles are compressed. The compaction density of particles can be calculated using ρ=m / v, where m is the mass of the particle (in grams) and v is the total volume of the compacted particles (in centimeters). 3 .

[0035] In some embodiments, the carbon-coated graphite anode material retains ≥80% of its capacity after 300 cycles under a 3.0 C discharge rate, which indicates that the carbon-coated graphite anode material in this application has excellent cycling performance under fast charging.

[0036] Furthermore, the full-cell system using carbon-coated graphite anode material was charged from 0% to 80% at a 3.0 C rate in 12 to 14 minutes. This demonstrates that the carbon-coated graphite anode material in this application exhibits excellent fast-charging performance.

[0037] A second aspect of this application provides a method for preparing the aforementioned carbon-coated graphite anode material, comprising: S10: The first carbon source is graphitized under an inert atmosphere to obtain graphite particles.

[0038] In this step, the first carbon source is heated to 2800℃~3200℃ (specifically, it can be 2800℃, 2900℃, 3000℃, 3100℃, 3200℃, etc.) under an inert atmosphere and held at that temperature for 5h~20h (specifically, it can be 5h, 10h, 15h, 20h, etc.) to perform high-temperature graphitization treatment, and graphite particles are obtained after cooling.

[0039] In some embodiments, before graphitizing the first carbon source, the first carbon source can be crushed and graded. The specific crushing method is not limited, but the particle size of the first carbon source after crushing is guaranteed to be 8 μm to 10 μm. The first carbon source mentioned above includes at least one of oil-based needle coke and coal-based needle coke, and the first carbon source can be selected according to the actual conditions.

[0040] S20: The graphite particles, the second carbon source, the nitrogen-containing precursor, the pore-forming agent and the catalyst are subjected to a sol-gel reaction to obtain the first carbon-coated graphite precursor.

[0041] In this step, a sol-gel reaction is carried out by placing graphite particles, a second carbon source, a nitrogen-containing precursor, a porogen, and a catalyst in a mixed solvent of water and ethanol. Specifically, the second carbon source and the nitrogen-containing precursor cross-link to form a film on the surface of the graphite particles under the action of the catalyst (that is, forming a carbon gel framework layer). After film formation, the porogen is embedded in the film and decomposes at a certain temperature (S30 in the following text) to produce small molecule gases such as CO2, NH3, and H2O. After the small molecule gases escape, they leave mesoporous channels in the carbon gel framework, thereby forming a mesoporous structure. At the same time, the second carbon source itself undergoes cross-linking and curing. During the cross-linking and curing process, molecular chain shrinkage occurs, forming micropores <2 nm.

[0042] In some embodiments, the mass ratio of graphite particles, second carbon source, nitrogen-containing precursor, pore-forming agent and catalyst is 100:(4~16):(0.3~3):(0.5~5):(0.1~1), specifically, it can be 100:(8~12):(0.5~2):(1~3):(0.2~0.8), for example, it can be 100:4:0.3:0.5:0.1, 100:4:1:3:0.5, 100:8:0.5:1:0.5, 100:12:2:3:0.6, 100:12:0.5:1:0.2, 100:12:0.5:1:0.8, 100:16:3:5:1, etc. The mass ratio within the above range can basically ensure that the carbon coating layer and the pore size of the micropores and mesopores in the carbon coating layer are within the target range of the negative electrode material.

[0043] In some embodiments, the second carbon source includes at least one selected from phenolic resin, epoxy resin, polyimide resin, furan resin, asphalt, polyvinyl alcohol, and glucose; the nitrogen-containing precursor includes at least one selected from dicyandiamide, melamine, urea, and C3N4; the porogen includes at least one selected from polyethylene glycol 2000, polyvinyl alcohol, Pluronic F127, ammonium bicarbonate, and citric acid; and the catalyst includes at least one selected from p-toluenesulfonic acid, oxalic acid, citric acid, hydrochloric acid, sulfuric acid, and phosphoric acid, preferably p-toluenesulfonic acid. The above substances can be selected according to actual conditions.

[0044] For example, when the second carbon source is phenolic resin, under the action of a catalyst, the hydroxymethyl group on the phenolic resin condenses with the active hydrogen on the phenolic ring. Simultaneously, the amino group in the nitrogen source condenses with the hydroxymethyl group of the phenolic resin. This results in cross-linking and film formation on the surface of the graphite particles, creating a carbon gel framework. The role of the catalyst is... Provide protons (H +Activating the hydroxymethyl groups in the phenolic resin accelerates the reaction, ensuring that the carbon gel framework forms a uniform film on the graphite particle surface rather than self-polymerizing in solution. Furthermore, during subsequent heat treatment, the porogen decomposes to generate small molecule gases. These gases form bubbles within the carbon gel framework, leaving behind mesoporous channels of 2-30 nm after escaping. Additionally, during the condensation of the hydroxymethyl groups on the phenolic resin with the active hydrogen on the phenolic ring, the molecular chains undergo dehydration and condensation, resulting in volume shrinkage and the formation of micropores <2 nm between chain segments.

[0045] In some embodiments, the temperature of the sol-gel reaction is 40℃~80℃ (specifically, it can be 40℃, 50℃, 60℃, 70℃, 80℃, etc.), and the reaction time is 2h~12h (specifically, it can be 2h, 4h, 6h, 8h, 10h, 12h, etc.). The above temperature range can basically ensure precise control of the crosslinking reaction between the second carbon source and the nitrogen-containing precursor, thereby ensuring film quality, and further ensuring the uniformity of the coating layer and the stability of the subsequent microporous structure.

[0046] S30: The first carbon-coated graphite precursor is subjected to gradient curing under vacuum to obtain the second carbon-coated graphite precursor.

[0047] In this step, the first graphite precursor is subjected to gradient curing under vacuum. During the gradient curing process, the pore-forming agent decomposes into small molecule gases such as CO2, NH3, and H2O. After the small molecule gases escape, they leave mesoporous channels in the carbon gel framework, thereby forming a mesoporous structure. At the same time, the second carbon source undergoes cross-linking curing. During the cross-linking curing process, molecular chain shrinkage occurs, thereby forming micropores <2 nm.

[0048] In some embodiments, the gradient curing treatment of the first graphite precursor under vacuum includes: 1. heating the first carbon-coated graphite precursor to a first temperature at a first heating rate and holding it at that temperature for a first time under vacuum conditions; 2. heating to a second temperature at a second heating rate and holding it at that temperature for a second time; 3. heating to a third temperature at a third heating rate and holding it at that temperature for a third time. At the first temperature, the second carbon sources in the carbon gel framework layer crosslink and solidify, transforming from a linear structure to a non-melting network structure, thus stabilizing the carbon gel framework layer on the surface of the graphite particles; at the second temperature, the second carbon sources further crosslink and solidify, and the network structure further transforms into a three-dimensional network structure, while the pore-forming agent begins to decompose or carbonize, generating a porous structure (mesoporous structure) in situ in the carbon gel framework layer; furthermore, at the third temperature, the cured carbon gel framework layer undergoes pyrolysis and carbonization, transforming into amorphous carbon, laying the foundation for subsequent high-temperature carbonization treatment.

[0049] Specifically, the first heating rate is 0.5℃ / min to 2℃ / min (specifically, it can be 0.5℃ / min, 1℃ / min, 1.5℃ / min, 2℃ / min, etc.), the first temperature is 160℃ to 240℃ (specifically, it can be 160℃, 180℃, 200℃, 220℃, 240℃, etc.), and the first time is 0.5h to 2h (specifically, it can be 0.5h, 1h, 1.5h, 2h, etc.); the second heating rate is 0.5℃ / min to 2℃ / min (specifically, it can be 0.5℃ / min, 1℃ / min, 1.5℃ / min, 2℃ / min, etc.). The second temperature is 360℃~520℃ (specifically, it can be 360℃, 400℃, 450℃, 500℃, 520℃, etc.), and the second time is 1h~3h (specifically, it can be 1h, 2h, 3h, etc.); the third heating rate is 0.5℃ / min~2℃ / min (specifically, it can be 0.5℃ / min, 1℃ / min, 1.5℃ / min, 2℃ / min, etc.), the third temperature is 580℃~650℃ (specifically, it can be 580℃, 600℃, 620℃, 650℃, etc.), and the third time is 5h~8h (specifically, it can be 5h, 6h, 7h, 8h, etc.). This ensures the reaction proceeds in steps, thereby ensuring the uniformity and stability of the micro-mesoporous structure in the second carbon-coated graphite precursor.

[0050] The gradient curing process described above, performed under vacuum, not only helps to reduce the temperature and time of the sol-gel reaction, but also helps to promote the timely removal of small molecule byproducts, which can significantly improve the density and uniformity of the carbon coating layer and reduce internal defects.

[0051] S40: The second carbon-coated graphite precursor is subjected to high-temperature carbonization treatment to obtain carbon-coated graphite anode material.

[0052] In this step, the second carbon-coated graphite precursor is subjected to high-temperature carbonization treatment, which transforms the film layer on the surface of the graphite particles into a carbon coating layer with high stability and strong conductivity. At the same time, the strength of the carbon coating layer and its bonding force with the graphite core are improved, thereby obtaining a carbon-coated graphite anode material with excellent rate performance and cycle stability.

[0053] In some embodiments, the high-temperature carbonization temperature is 800℃~1150℃ (specifically, it can be 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, etc.); the high-temperature carbonization time is 3h~5h (specifically, it can be 3h, 3.5h, 4h, 4.5h, 5h, etc.). Therefore, it can be basically guaranteed that the second carbon-coated graphite precursor is transformed into a carbon-coated graphite anode material with high stability, strong conductivity, and excellent rate performance and cycle stability.

[0054] Furthermore, the heating rate for high-temperature carbonization ranges from 1.0℃ / min to 6.0℃ / min, specifically 1.0℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, and 6℃ / min. This ensures that the second carbon-coated graphite precursor is heated uniformly, contributing to the obtaining of highly stable carbon-coated graphite anode materials.

[0055] A third aspect of this application provides a negative electrode sheet comprising the aforementioned carbon-coated graphite negative electrode material. Specifically, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer comprising the aforementioned carbon-coated graphite negative electrode material. Thus, this negative electrode sheet possesses all the advantages of carbon-coated graphite negative electrode materials, which will not be elaborated upon here.

[0056] As an example, the negative electrode material layer also includes at least one of a thickener, a conductive agent, and a binder. Specifically, the negative electrode current collector can be a metal foil, for example, copper foil. The binder in the negative electrode material layer can include, but is not limited to, at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethyl methacrylate (PMAA), and carboxymethyl chitosan (CMCS). The conductive agent in the negative electrode material layer can include, but is not limited to, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0057] A fourth aspect of this application provides a battery comprising the aforementioned carbon-coated graphite anode material or the aforementioned anode sheet. Therefore, this battery exhibits excellent fast-charging performance.

[0058] In some embodiments, the battery further includes a positive electrode, an electrolyte, and a separator. The positive electrode, negative electrode, and separator are all immersed in the electrolyte. During the charging and discharging process of the battery, active ions are inserted and extracted back and forth between the positive and negative electrodes. The electrolyte plays the role of conducting ions between the positive and negative electrodes. The separator is disposed between the positive and negative electrodes and mainly plays the role of preventing short circuits between the positive and negative electrodes, while allowing active ions to pass through.

[0059] It is understood that the positive electrode sheet may include a current collector and a positive electrode material layer disposed on at least one surface of the current collector. The positive electrode material layer may include a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder, and may also include additives with specific functions and effects, such as lithium supplements, film-forming additives, flame retardants, high-temperature / low-temperature stabilizers, etc., as needed.

[0060] In some embodiments, the positive current collector can be a metal current collector or a composite current collector. For example, metal current collectors include, but are not limited to, aluminum foil current collectors; composite current collectors may include a polymer base layer (such as a base layer of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.) and a metal layer (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) formed on at least one surface of the polymer base film.

[0061] In some embodiments of this application, the positive electrode active material may include at least one of the following: layered positive electrode active materials (e.g., nickel-cobalt-manganese ternary positive electrode materials, nickel-cobalt-aluminum ternary positive electrode materials, lithium nickel oxide / sodium, lithium cobalt oxide / sodium, lithium manganese oxide / sodium, lithium-rich / sodium layered and rock salt phase layered materials), olivine-type phosphate active materials (e.g., lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, etc.), and spinel-structured positive electrode active materials (e.g., spinel lithium manganese oxide, spinel lithium nickel manganese oxide, lithium-rich spinel lithium manganese oxide, and lithium nickel manganese oxide, etc.). It is understood that the above-mentioned positive electrode active materials may further include doping elements and coating layers. As a specific example, the positive electrode active material includes lithium iron phosphate. Therefore, the lithium-ion battery has better cycle stability and safety performance.

[0062] In some embodiments of this application, the positive electrode adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a terpolymer of PVDF-tetrafluoroethylene-propylene, a terpolymer of PVDF-hexafluoropropylene-tetrafluoroethylene, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorinated acrylate resin. This allows for better adhesion of the positive electrode material layer to the positive electrode current collector, resulting in stronger adhesion and reducing the likelihood of problems such as positive electrode dressing detachment.

[0063] In some embodiments of this application, the positive electrode conductive agent may include at least one selected from superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. This effectively improves conductivity, reduces internal resistance, and enhances the electrochemical performance of lithium-ion batteries.

[0064] In some embodiments, the separator may be a separator known in the art that can be used in lithium-ion batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, etc.

[0065] According to embodiments of this application, the electrolyte may include lithium salt and solvent. Furthermore, additives with specific functions, such as film-forming additives, lithium replenishing agents, flame retardants, thermal stability additives, etc., may also be added to the electrolyte as needed. As an example, the electrolyte may include lithium salt, solvent, and additives.

[0066] In some embodiments of this application, the lithium salt may include at least one of LiPF6, LiFSI, and LiTFSI. The lithium salt can provide lithium ions to the battery, support the stability of the electrolyte and electrochemical reactions, help form a protective SEI film, improve conductivity, and enhance the safety of the lithium-ion battery.

[0067] According to embodiments of this application, the solvent may include carbonates, fluorocarbonates, etc. This allows for the sufficient dissolution of lithium salts, provides an ion transport medium, and also helps improve the electrochemical and safety performance of lithium-rich manganese-based batteries.

[0068] According to the embodiments of this application, the battery can be a single cell, a battery module, or a battery pack. The specific structure of the battery module or battery pack is not particularly limited and can be carried out with reference to conventional techniques in the art.

[0069] In a fifth aspect of this application, an electrical device is proposed, comprising the aforementioned battery. Consequently, this battery exhibits excellent fast-charging performance and a long service life.

[0070] In some embodiments of this application, the specific type of electrical device is not particularly limited and can be any device that uses a battery as a power source or energy storage unit. For example, electrical devices include, but are not limited to, electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), mobile terminals (e.g., mobile phones, laptops, game consoles, wearable devices, etc.), drones, aerospace equipment, satellites, ships, energy storage systems, and so on.

[0071] It is understood that, in addition to the battery mentioned above, the electrical device also includes other necessary structures and components, all of which can be made with reference to conventional technologies. For example, an electric vehicle may include a body, chassis, tires, navigation system, radar system, steering system, braking system, lubrication system, cooling system, driving system, etc., which will not be described in detail here.

[0072] The present application will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present application in any way. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or in accordance with the product manual.

[0073] Example 1 The carbon-coated graphite anode material was prepared according to the preparation method of this application, as follows: S10: The oil-based needle coke was graphitized under a nitrogen atmosphere. Specifically, the graphitization temperature was 3000℃ and the treatment time was 10h. After the graphitization treatment, the sample was cooled and crushed to obtain graphite particles with a particle size of about 8~10 μm.

[0074] S20: The graphite particles obtained above, phenolic resin (second carbon source), melamine (nitrogen-containing precursor), ammonium bicarbonate (porogen), and p-toluenesulfonic acid (catalyst) are mixed in a mixed solvent of water and ethanol at a mass ratio of 100:10:1:2:0.5 (volume ratio of ethanol to water is 1:1) to carry out a sol-gel reaction. Specifically, the temperature of the sol-gel reaction is 60℃ and the reaction time is 8h to obtain the first carbon-coated graphite precursor.

[0075] S30: The first graphite precursor is subjected to gradient curing treatment at -0.07 MPa (first temperature 200℃, first time 1h, second temperature 450℃, second time 2h, third temperature 620℃). The third time was 6 hours, and the heating rate was 1℃ / min, to obtain the second carbon-coated graphite precursor; S40: The second carbon-coated graphite precursor is subjected to high-temperature carbonization treatment (the temperature of the high-temperature carbonization treatment is 1000℃, the time of the high-temperature carbonization treatment is 4h, and the heating rate of the high-temperature carbonization treatment is 3℃ / min), and after cooling to room temperature, it is demagnetized to obtain the carbon-coated graphite anode material.

[0076] Preparation of the positive electrode sheet: A ternary positive electrode material, conductive agent, binder, and dispersant were mixed in a mass ratio of 96.8:1.5:1.5:0.2. The mixture was first dry-mixed, then a suitable amount of NMP (N-methylpyrrolidone) was added and wet-mixed to obtain a positive electrode slurry. The solid content of the positive electrode slurry was controlled to be 65%. Further, the positive electrode slurry was coated onto a 14μm thick carbon-coated aluminum foil (where the aluminum foil thickness was 12 micrometers, and each side of the aluminum foil was coated with a 1-micrometer thick carbon layer), resulting in a double-sided areal density of 40 mg / cm³ for the positive electrode sheet. 2 After drying at 100℃, the resulting positive electrode sheet is dried. Finally, the dried positive electrode sheet is rolled to achieve a compaction density of 2.30 g / cm³. 3 The prepared positive electrode sheet is die-cut according to the cell size and placed in a nitrogen oven at 100℃ for later use. Preparation of the negative electrode: A slurry was prepared according to the following mass ratio: carbon-coated graphite negative electrode material: FG-5 (conductive adhesive): CMC: SBR: PAA 96.5:1.2:0.4:0.5:2.5. The mixture was first dry-mixed, and then a suitable amount of solvent was added for wet mixing to obtain the negative electrode slurry. The solid content of the negative electrode slurry was controlled to be 55%. Then, the negative electrode slurry was coated on a 6μm thick copper foil to achieve a double-sided areal density of 13mg / cm². 2 The negative electrode sheet is dried at 80℃. Finally, the dried negative electrode sheet is rolled to achieve a compaction density of 1.50 g / cm³. 3 Then, the rolled negative electrode sheet is die-cut according to the cell size and placed in a nitrogen oven at 90℃ for later use. Lithium-ion battery assembly: A stacking process is used, requiring one more negative electrode than positive electrode. The number of electrodes is calculated based on a design capacity of 1Ah. The electrodes are stacked in the order of separator, negative electrode, separator, positive electrode, separator, and negative electrode. After hot pressing, tab welding, and encapsulation, the moisture content is controlled below 400ppm. Electrolyte is injected according to the design capacity, with an injection coefficient of 4.0g / Ah.

[0077] Examples 2-7 Same as Example 1, the main differences are shown in Table 1 and Table 2.

[0078] Examples 8-9 Same as Example 1, the main differences are shown in Tables 1 and 2, and the second carbon source is pitch.

[0079] Examples 10-11 Same as Example 1, the main differences are shown in Tables 1 and 2, and the pore-forming agent is polyethylene glycol.

[0080] Examples 12-13 Same as Example 1, the main differences are shown in Tables 1 and 2, and the nitrogen-containing precursor is dicyandiamide.

[0081] Examples 14-15 Same as Example 1, the main differences are shown in Tables 1 and 2, and the catalyst is oxalic acid.

[0082] Examples 16-17 Same as Example 1, the main differences are shown in Table 1 and Table 2.

[0083] Comparative Example 1 Same as Example 1, the main difference being that no porogen was added.

[0084] Comparative Example 2 Similar to Example 1, the main difference is that the obtained graphite particles with a particle size of about 8~10 μm are demagnetized and then directly used as negative electrode active materials to prepare negative electrode sheets.

[0085] Detection methods The performance of the negative electrode materials prepared in Examples 1-17 and Comparative Examples 1-2, as well as the electrochemical performance of the lithium-ion batteries, were tested.

[0086] Capacity retention rate: At a temperature of 25℃±5℃, the battery capacity retention rate was recorded after 300 cycles under discharge conditions of 3.0 C and 1.0 C. The specific process is as follows: ① Charging stage: Charged at 1C constant current to 4.2V; ② Constant voltage charging stage: Charged at constant voltage to 0.05C; ③ Rest for 30min; ④ Discharge stage: For 1C discharge, discharged at 1C constant current to 2.5V; For 3C discharge, discharged at 3C constant current to 2.5V; ⑤ Rest for 30min; ⑥ Repeated cycles: Repeated steps ①-⑤ for a total of 300 cycles. Capacity retention rate calculation: Recorded the discharge capacity of each cycle. Capacity retention rate (%) = (Discharge capacity of the 300th cycle / Discharge capacity of the 1st cycle) × 100%.

[0087] The full-cell system using the aforementioned carbon-coated graphite anode material was charged from 0% to 80% at a 3.0 C rate using the following steps: discharging at 0.33C to the lower limit voltage (considered 0% SOC), resting for 5 minutes, and then charging at a constant current rate (3.0C) until the charged capacity was 0.8 × C0 (i.e., reaching 80% SOC, where C0 is the rated capacity). The time elapsed from the start of charging to reaching 80% SOC was recorded.

[0088] The BET (Body Surface Area) and pore size distribution were characterized using an ASAP2020 nitrogen surface adsorption-desorption instrument. Specifically, the sample was adsorbed with nitrogen at low temperature (typically 77 K), and the pressure changes of the sample and the desorbed gas were recorded under reduced pressure to obtain structural parameters such as the specific surface area and pore size distribution of the sample.

[0089] Test Results The performance of the carbon-coated graphite anode materials prepared in Examples 1-17 and Comparative Examples 1-2, as well as the electrochemical performance of the lithium-ion batteries, are shown in Tables 2 and 3.

[0090] Furthermore, the N1s spectrum of the carbon-coated graphite anode material obtained in Example 1 is shown below. Figure 2 It can be seen that nitrogen was successfully doped into the carbon coating layer, forming nitrogen species with different configurations such as pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen. The introduction of nitrogen atoms can increase the carrier concentration and migration rate, which is beneficial for the rapid transfer of electrons during the charging and discharging process of the electrode.

[0091] The pore size distribution of the carbon coating layer in the carbon-coated graphite anode material prepared in Example 1 was tested, see [see details]. Figure 3 It can be seen that there are continuous non-zero values ​​and small bumps in the <2 nm region, and the data points are continuous and form small peaks, indicating the presence of micropores; a complete broad peak is presented in the 3~30 nm range, with the peak value located at about 7 nm, indicating the presence of a large number of mesopores. The pore size distribution of the carbon coating layer in the carbon-coated graphite anode material prepared in Comparative Example 1 was tested, see [see figure]. Figure 4 It can be seen that the sample has no pores in the <2 nm region, proving that there are no micropores.

[0092]

[0093]

[0094]

[0095] Conclusion: The results of Examples 1-17 and Comparative Examples 1-2 show that the negative electrode material has a carbon coating layer with a porous structure, which can effectively improve the electrochemical performance (fast charging performance and cycle performance) of the battery.

[0096] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this invention and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.

[0097] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0098] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection, an electrical connection, or a connection that allows communication between them; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components, unless otherwise explicitly limited. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0099] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0100] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0101] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A carbon-coated graphite anode material, characterized in that, The material includes carbon-coated graphite anode material particles, which comprise a graphite core and a carbon coating layer. The carbon coating layer has a multi-level porous structure, including micropores and mesopores, and is doped with nitrogen.

2. The carbon-coated graphite anode material according to claim 1, characterized in that, At least one of the following conditions must be met: The thickness of the carbon coating layer is 100nm~200nm; The pore size of the micropores in the carbon coating layer is <2nm; The pore size of the intermediate pores in the carbon coating layer is 2nm~30nm.

3. The carbon-coated graphite anode material according to claim 1, characterized in that, At least one of the following conditions must be met: The carbon-coated graphite anode material D 50 Particle size ranges from 10 μm to 30 μm; The specific surface area of ​​the carbon-coated graphite anode material is 2.0 m². 2 / g~3.5m 2 / g; The compaction density of the carbon-coated graphite anode material is 1.5 g / cm³. 3 ~1.9 g / cm 3 ; The degree of graphitization of the carbon-coated graphite anode material is 91%~95%.

4. The carbon-coated graphite anode material according to any one of claims 1 to 3, characterized in that, At least one of the following conditions must be met: The carbon-coated graphite anode material retains ≥80% of its capacity after 300 cycles under a 3.0 C discharge rate. The full-cell system using the carbon-coated graphite anode material takes 12 to 14 minutes to charge from 0% to 80% at a 3.0 C rate.

5. A method for preparing a carbon-coated graphite anode material as described in any one of claims 1 to 4, characterized in that, include: The first carbon source was graphitized under an inert atmosphere to obtain graphite particles. The graphite particles, the second carbon source, the nitrogen-containing precursor, the pore-forming agent, and the catalyst are subjected to a sol-gel reaction to obtain a first carbon-coated graphite precursor. The first carbon-coated graphite precursor was subjected to gradient curing under vacuum to obtain the second carbon-coated graphite precursor. The second carbon-coated graphite precursor is subjected to high-temperature carbonization treatment to obtain a carbon-coated graphite anode material.

6. The preparation method according to claim 5, characterized in that, At least one of the following conditions must be met: The mass ratio of the graphite particles, the second carbon source, the nitrogen-containing precursor, the porogen, and the catalyst is 100:(4~16):(0.3~3):(0.5~5):(0.1~1), preferably 100:(8~12):(0.5~2):(1~3):(0.2~0.8). The temperature for the graphitization treatment is 2800℃~3200℃; The graphitization process takes 5 to 20 hours. The temperature for the sol-gel reaction is 40℃~80℃; The sol-gel reaction time is 2h~12h; The high-temperature carbonization temperature is 800℃~1150℃; The high-temperature carbonization time is 3h~5h; The heating rate for the high-temperature carbonization is 1.0℃ / min to 6.0℃ / min; The first carbon source includes at least one of oil-based needle coke and coal-based needle coke; The second carbon source includes at least one of phenolic resin, epoxy resin, polyimide resin, furan resin, asphalt, polyvinyl alcohol, and glucose; The nitrogen-containing precursor includes at least one of dicyandiamide, melamine, urea, and C3N4; The pore-forming agent includes at least one of polyethylene glycol 2000, polyvinyl alcohol, Pluronic F127, ammonium bicarbonate, and citric acid. The catalyst includes at least one of p-toluenesulfonic acid, oxalic acid, citric acid, hydrochloric acid, sulfuric acid, and phosphoric acid, preferably p-toluenesulfonic acid.

7. The preparation method according to claim 5, characterized in that, The first carbon-coated graphite precursor is subjected to gradient curing under vacuum, which includes: The first carbon-coated graphite precursor is heated to a first temperature at a first heating rate and held for a first time under vacuum conditions. Heat to the second temperature at the second heating rate and hold for the second time; Heat to the third temperature at the third heating rate and hold for the third time.

8. The preparation method according to claim 7, characterized in that, At least one of the following conditions must be met: The first heating rate is 0.5℃ / min to 2℃ / min; The first temperature is 160℃~240℃; The first time period is 0.5h to 2h; The second heating rate is 0.5℃ / min to 2℃ / min; The second temperature is 360℃~520℃; The second time period is 1 hour to 3 hours; The third heating rate is 0.5℃ / min to 2℃ / min; The third temperature is 580℃~650℃; The third time period is 5h~8h; The vacuum conditions are -0.08 MPa to -0.06 MPa.

9. A negative electrode sheet, characterized in that, Includes the carbon-coated graphite anode material as described in any one of claims 1 to 4.

10. A battery, characterized in that, Includes the carbon-coated graphite anode material as described in any one of claims 1 to 4 or the anode sheet as described in claim 9.

11. An electrical appliance, characterized in that, Includes the battery as described in claim 10.